1992
DOI: 10.1111/j.1476-5381.1992.tb14215.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor synthesis by peritoneal mast cells and its inhibition by two quinoline‐based compounds

Abstract: 1 Peritoneal mast cells from rat were co-incubated in vitro in a platelet aggregometer cuvette with washed rabbit platelets. In response to stimulation with calcium ionophore (A23187; 1-5 ,UM), the mast cells released a substance which stimulated the platelets to aggregate. These concentrations of ionophore did not stimulate platelet aggregation in the absence of mast cells, nor affect the responsiveness of the platelets to aggregation induced by thrombin or PAF. Release of a PAF-like substance was also observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Of particular interest is the recent finding that PF 5901 will also inhibit PAF synthesis in rodent mast cells (Hogaboam et al, 1992). In recent studies, LTC4, LTD4 and LTE4 have been shown to increase airway responsiveness to histamine in asthmatic but not normal subjects (Arm et al, 1988;O'Hickey et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the recent finding that PF 5901 will also inhibit PAF synthesis in rodent mast cells (Hogaboam et al, 1992). In recent studies, LTC4, LTD4 and LTE4 have been shown to increase airway responsiveness to histamine in asthmatic but not normal subjects (Arm et al, 1988;O'Hickey et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular leaks have been shown to occur after treatment with histamine (2,25,26), leukotriene B4 and C4 (16) endothelin 3 (15), platelet-activating factor (PAF), and hydroxytrytomine (20). Plateletactivating factor and histamine are two products which are released when mesenteric mast cells degranulate (5,10). Thus, factors that stimulate degranulation of mast cells could lead to additional increases in microvascular permeability beyond those produced by the particular experimental pertubation.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activating factor also has ulcerogenic effects and has been proposed to be important in gastric ulcerogenesis from necrotizing agents (Wallace 1990). The inter-relationships between the metabolism of arachidonate and platelet-activating factor (Carlini et al 1985;Hogaboam et al 1992) and the activation of their metabolism by calcium (O'Flaherty 1988) suggests there are important interactions amongst all three of these mediators of potential importance in ulcerogenesis. Calcium antagonists have been shown to prevent ethanol-and indomethacin-induced gastric lesions in normal rats (Ghanayem et al 1987).…”
mentioning
confidence: 99%